2021
DOI: 10.1111/apa.15716
|View full text |Cite
|
Sign up to set email alerts
|

Delivery room cuddles for extremely preterm babies and parents: concept, practice, safety, parental feedback

Abstract: Aim Following extreme preterm birth, there has traditionally been felt an imperative to rush baby to the neonatal unit for ongoing intensive care. Immediate needs of parents to bond with their babies through direct early physical contact have often been overlooked; many weeks can pass before parents get to hold their babies for the first time. Recognition of the importance of early contact is growing. We aimed to review the safety and value of routinely practising delivery room cuddles for extremely preterm ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Earlier literature shows that an educationalbehavioural intervention program to enhance mothers' participation improved motherinfant interactions scores [35]. Recent literature has reported very positive and meaningful parental experiences related to immediate physical parent-infant closeness among parents of very preterm infants [36][37][38][39]. In addition, immediate skin-to-skin contact was associated with less impaired bonding in a randomised controlled trial including infants born between 25 and 32 weeks of gestation [40].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier literature shows that an educationalbehavioural intervention program to enhance mothers' participation improved motherinfant interactions scores [35]. Recent literature has reported very positive and meaningful parental experiences related to immediate physical parent-infant closeness among parents of very preterm infants [36][37][38][39]. In addition, immediate skin-to-skin contact was associated with less impaired bonding in a randomised controlled trial including infants born between 25 and 32 weeks of gestation [40].…”
Section: Discussionmentioning
confidence: 99%
“…To date, one other study in the UK has explored parent experience associated with delivery room cuddles. Clarke et al, using a parent questionnaire design, also reported parental associated feelings including relief, reassurance, pride and love, fear and anxiety 26 …”
Section: Discussionmentioning
confidence: 99%
“…Clarke et al, using a parent questionnaire design, also reported parental associated feelings including relief, reassurance, pride and love, fear and anxiety. 26 The qualitative design approach used in this project has enabled us to deepen our understanding of the emotional touchpoints associated with the delivery room cuddle and also captures the continuum of emotions that are imbued in the delivery of a high-risk infant.…”
Section: Discussionmentioning
confidence: 99%
“…A RCT in Germany reported less impaired bonding and improved motor and vocal development of the infant, as well as reduced expression in studied stress-related genes in the group receiving immediate skin-to-skin contact, compared to conventional care after a very preterm birth [ 16 , 17 ]. The feasibility, safety and positive parental experiences of “delivery room cuddle”, in which the mother holds her extremely preterm or sick infant for a brief period of time prior to the admission to the neonatal intensive care unit (neonatal unit), have been reported by different study groups in the United Kingdom [ 18 20 ]. Non-separation can be attained, and it is preferred by parents, also during the resuscitation of the infant if the stabilization procedure is performed near the mother in the labor ward/operating room [ 21 23 ].…”
Section: Rationale and Evidencementioning
confidence: 99%